One-shot LC–MS/MS analysis of post-translational modifications including oxidation and deamidation of rat lens α- and β-crystallins induced by γ-irradiation - Kim, Ingu; Saito, Takeshi; Fujii, Norihiko; Kanamoto, Takashi; Fujii, Noriko (Amino acids, 2016)
The eye lens is a transparent organ that functions to focus light and images on the retina. The transparency and high refraction of the lens are maintained by the function of α-, β-, and γ-crystallins. These long-lived proteins are subject to various post-translational modifications, such as oxidation, deamidation, truncation and isomerization, which occur gradually during the aging process. Such modifications, which are generated by UV light and oxidative stress, decrease crystallin solubility and lens transparency, and ultimately lead to the development of age-related cataracts. Here, we irradiated young rat lenses with γ-rays (5–500 Gy) and extracted the water-soluble (WS) and water-insoluble (WI) protein fractions. The WS and WI lens proteins were digested with trypsin, and the resulting peptides were analyzed by one-shot LC–MS/MS to determine the specific sites of oxidation of methionine and tryptophan, deamidation sites of asparagine and glutamine, and isomerization of aspartyl in rat α- and β-crystallins in the WS and WI fractions. Oxidation and deamidation occurred in several crystallins after irradiation at more than, respectively, 50 and 5 Gy; however, isomerization did not occur in any crystallin even after exposure to 500 Gy of irradiation. The number of oxidation and deamidation sites was much higher in the WI than in the WS fraction. Furthermore, the oxidation and deamidation sites in rat crystallins resemble those reported in crystallins from human age-related cataracts. Thus, this study on post-translational modifications of crystallins induced by ionizing irradiation may provide useful information relevant to the formation of human age-related cataracts.